PENDAMPINGAN MASYARAKAT DALAM PEMBUATAN PUPUK ORGANIK DARI LIMBAH TERNAK DI DUKUH CENTHONG, DESA NGADIROJO - Vellia Ekaprasti; Dyah Rismawati; Lutfi Nurrokhimah; Rida Ramadhani; Ratu Tata Mulia; Yusup Arip (Jurnal Terapan Ekonomi dan Bisnis, 2025)
The Community Service Program (Kuliah Kerja Nyata/KKN) is a form of student engagement aimed at addressing local issues through solution-oriented activities. One of the key problems in Dukuh Centhong, Ngadirojo Village, is the underutilization of livestock waste, which in fact holds great potential as organic fertilizer. Excessive use of chemical fertilizers has negative impacts on soil fertility and ecosystems, making environmentally friendly alternatives necessary. This community service activity was carried out by Group 9 of the KKN students from Universitas Muhammadiyah Ponorogo on August 13, 2025, with the aim of providing education and assistance in producing organic fertilizer from livestock waste. The implementation methods included a counseling session on the benefits of organic fertilizer and hands-on practice in fermenting livestock manure using a natural fermentator made from fruit extracts and other supporting materials. The results showed a high level of enthusiasm among residents, who were able to independently apply the organic fertilizer production techniques. This program is expected to help reduce livestock waste, improve soil fertility, and create economic opportunities for the community through the use of organic fertilizer